Kondisi Kualitas Air Perairan Punagayya Dalam Menunjang Keberlanjutan Budidaya Rumput Laut (Kappaphycus alvarezii) - Mulyawan, Ardi Eko; Hafid, Hasriyani; Hidayani, Mesalina Tri; Susilowati, Aryanti (Universitas Musamus, Merauke, Papua, 2021)
Punagaya waters are one of the seaweed cultivation locations in Jeneponto Regency. In 2005, a power plant was built at that location. This development has raised concerns, especially for seaweed farmers in the area. The sustainability of seaweed cultivation and production in Punagaya waters is primarily determined by the water quality and several other related aspects. The purpose of this study was to find information on the physical and chemical conditions of Punagaya waters used for seaweed cultivation after the construction of the power plant (PLTU) and the possibility of contamination of Plumbum (Pb) and Cadmium (Cd). Samples for physical and chemical measurements of seawater were carried out in-situ at the study site, while the chemical analysis of water in the form of nitrate, phosphate, plumbum (Pb) and cadmium (Cd) was carried out in the laboratory. The results showed that the physical and chemical conditions of the Punagaya waters used for seaweed cultivation after the PLTU construction were still within the permissible limits for seaweed cultivation. However, it needs to be aware of the high-temperature value. The value of heavy metals is still in the lower limit for cultivation for seaweed.